2011
DOI: 10.1007/s10549-011-1757-y
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase genotype (Val158met) modulates cancer-related fatigue and pain sensitivity in breast cancer survivors

Abstract: Cancer-related fatigue and pain after surgery are the most frequent and most incapacitating cancer-related symptoms after breast cancer treatment. Genetic influence of cancer-related fatigue and pain has not been previously investigated. Our aim was to examine the influence of catechol-O-methyltransferase (COMT) Val158Met genotypes on cancer-related fatigue, post-mastectomy pain, and pressure pain hypersensitivity in breast cancer survivors. One-hundred and twenty-eight (n = 128) breast cancer survivors who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…1 The included studies examined the genetic associations underlying one of the four treatment-induced toxicities, cardiotoxicity (N = 5), cognitive dysfunction (N = 2), fatigue (N = 4) and peripheral neuropathy (N = 8) [11,12,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Table 1 summarizes the genetic variants that were positively associated with each toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The included studies examined the genetic associations underlying one of the four treatment-induced toxicities, cardiotoxicity (N = 5), cognitive dysfunction (N = 2), fatigue (N = 4) and peripheral neuropathy (N = 8) [11,12,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Table 1 summarizes the genetic variants that were positively associated with each toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue (Table 5) Four of the studies examined the genetic associations underlying fatigue [33][34][35][36]. The COMT gene and the genes expressing proinflammatory cytokines were investigated (IL1B-511, IL6-174, TNF-308, IL6R and C-reactive protein).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study [63] has revealed an association between catechol-O-methyltransferase (COMT) gene and the risk for having fatigue in breast cancer patients following breast surgery. Patients with homozygous (Met/Met) or heterozygous (Val/Met) for COMT allele variant (rs4680) had higher fatigue scores when compared with those carrying the wild type (Val/ Val).…”
Section: Neurotransmitter Genes and Fatigue And Energymentioning
confidence: 99%
“…While polymorphisms in COMT and SLC6A4 have been previously linked with fatigue [63,64], other SNPs and/or haplotypes in ADRB2, BDNF, CYP3A4, GALR1, GCH1, NPY1R HapA04, SLC6A1, SLC6A2, SLC6A3, NOS1 and TAC1 are being linked to fatigue or energy or both for the first time in breast cancer patients [53]. Of note is the presence of the three genes (NOS1, SLC6A2 and SLC6A4) that were associated with both fatigue and energy, thus further strengthening the hypothesis that fatigue and energy level though commonly grouped together are distinct symptoms.…”
Section: Neurotransmitter Genes and Fatigue And Energymentioning
confidence: 99%
See 1 more Smart Citation